2019
DOI: 10.1111/jocs.14299
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms and risk classification systems predicting overall and cancer‐specific survival in primary malignant cardiac tumor

Abstract: Background: Primary malignant cardiac tumors (PMCTs) are fatal, but up to now, there is still a lack of survival prediction model for prognosis evaluation. We developed nomograms to predict overall survival (OS) and cancer-specific survival (CSS) for PMCTs by the Surveillance, Epidemiology, and End Result (SEER) database.Methods: A total of 506 PMCTs participants were identified in the SEER database from 1973 to 2014 and were randomly assigned into the training cohort (N = 354) and the validation cohort (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…Based on the maximum χ 2 and minimum P value in the X-tile software (18), the optimal cut-off value for age in PMCTs patients was objectively identified as 44 and 76 in the current study, which is considered to be more credible and accurate. In previous studies on PMCTs patients, age at diagnosis showed a strong prognostic association with OS (4,19). In our study, older age was found to be associated with higher odds of early mortality, with patients over 76-year old having the highest odds of early mortality, followed by the 44-76 age group and 44, which was similar to the optical age cut-off value for OS for PMCT patients (4).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the maximum χ 2 and minimum P value in the X-tile software (18), the optimal cut-off value for age in PMCTs patients was objectively identified as 44 and 76 in the current study, which is considered to be more credible and accurate. In previous studies on PMCTs patients, age at diagnosis showed a strong prognostic association with OS (4,19). In our study, older age was found to be associated with higher odds of early mortality, with patients over 76-year old having the highest odds of early mortality, followed by the 44-76 age group and 44, which was similar to the optical age cut-off value for OS for PMCT patients (4).…”
Section: Discussionsupporting
confidence: 85%
“…Lymphoma is the main pathological type of malignant cardiac tumor and is sensitivity to chemotherapy making this the primary treatment modality (29,30). Sarcoma is also believed to benefit from chemotherapy treatment (4,31,32). In our study, chemotherapy was found to be significantly associated with a decreased incidence of early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The validation of the nomogram model was evaluated using the Harrell's concordance index (C-index), calibration curves, and decision curve analyses (DCAs). C-index values ≥0.7 indicate a comparatively accurate prediction in general (17,18). Calibration curves (bootstrap analyses with 1,000 resamples) were integrated to test the calibration of the nomogram model, and DCAs were further used to evaluate the usefulness of the model constructed by previous steps.…”
Section: Discussionmentioning
confidence: 99%
“…After the inclusion and exclusion criteria, there were 152 non-LAA stroke patients were admitted to the study. In previous studies, it is common and suitable to include 2/3-4/5 patients as the development group (Gao et al 2020;Du 2020;Wang 2020;Guan 2019). In our study, we used R (packge caret) to randomly select 2/3 of the patients as the development group, and the remaining patients as the validation group.…”
Section: Methodsmentioning
confidence: 99%